2023
DOI: 10.3389/fgene.2022.1097234
|View full text |Cite
|
Sign up to set email alerts
|

A novel 9-gene signature for the prediction of postoperative recurrence in stage II/III colorectal cancer

Abstract: Background: Individualized recurrence risk prediction in patients with stage II/III colorectal cancer (CRC) is crucial for making postoperative treatment decisions. However, there is still a lack of effective approaches for identifying patients with stage II and III CRC at a high risk of recurrence. In this study, we aimed to establish a credible gene model for improving the risk assessment of patients with stage II/III CRC.Methods: Recurrence-free survival (RFS)-related genes were screened using Univariate Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The researchers found that the long-term survival rates among older patients were similar to those observed in their younger counterparts [ 38 ]. In a 2019 study by Ju et al, there was an emphasis on the importance of improving individual recurrence risk prediction for stage II/III colorectal cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that the long-term survival rates among older patients were similar to those observed in their younger counterparts [ 38 ]. In a 2019 study by Ju et al, there was an emphasis on the importance of improving individual recurrence risk prediction for stage II/III colorectal cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In CRC, it has been shown to be an RNA-binding gene associated with patient survival [ 35 , 36 ]. Prior studies have provided evidence that the expression of INHBB and the OS probability of CRC were negatively correlated [ 37–39 ]. Intriguingly, research has confirmed the association of INHBB with DNA methylation changes in CRC, indicating that it is also a potential biomarker related to methylation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…SPINK1 pathogenic variant has been identified in pancreatic ductal adenocarcinoma [5]. A gene set including SPINK1 was identified to predict postoperative recurrence in stage II/III colorectal cancer [6]. SPINK1, over expressed in TMPRSS2:ERG-negative prostate cancer, was detected in urine cell-sediment of prostate cancer [7].…”
Section: Introductionmentioning
confidence: 99%